Exploring Arsenic Transformation and Chemotaxis in a Pseudomonas sp. - Pankaj Kumar Arora; Sneha Gangwar; Pushpendra Sagar; Sandeep Gangwar; Alok Srivastava; Sanjay Kumar Garg; Vijay Kumar Sinhal; Vijay Pal Singh (Journal of Pure and Applied Microbiology)
An arsenic-resistant bacteria (strain PKA 200) was isolated from the Hindon River (Ghaziabad) after analyzing its water sample. Strain PKA 200 belongs to the Pseudomonas genus and can convert harmful arsenite [As (III)] into less harmful arsenate [As(V)]. Strain PKA 200 exhibits a remarkable ability to sense and move towards arsenite. Strain PKA 200 is a promising candidate for studying how bacteria sense and transform arsenic. Here, we report a novel circular plate assay to demonstrate both chemotaxis and biotransformation of arsenite by Pseudomonas sp. PKA 200.